Regulators of mitochondrial dynamics in cancer. (April 2016) - Senft, Daniela; Ronai, Ze'ev A
Graphical abstract: Highlights: The interplay of regulators of mitophagy, mitochondrial dynamics, and apoptosis controls cell fate. Mitochondrial dynamics impacts transformation, stemness, and cancer cell migration. Ubiquitin ligases deregulated in cancer control mitochondrial morphology. Abstract : Mitochondrial dynamics encompasses processes associated with mitochondrial fission and fusion, affecting their number, degree of biogenesis, and the induction of mitophagy. These activities determine the balance between mitochondrial energy production and cell death programs. Processes governing mitochondrial dynamics are tightly controlled in physiological conditions and are often deregulated in cancer. Mitochondrial protein homeostasis, transcriptional regulation, and post-translational modification are among processes that govern the control of mitochondrial dynamics. Cancer cells alter mitochondrial dynamics to resist apoptosis and adjust their bioenergetic and biosynthetic needs to support tumor initiating and transformation properties including proliferation, migration, and therapeutic resistance. This review focuses on key regulators of mitochondrial dynamics and their role in cancer.